Development of perceived competence, tactical skills, motivation, technical skills, and speed and agility in young soccer players - Forsman, H.; Gråstén, A.; Blomqvist, M.; Davids, K.; Liukkonen, J.; Konttinen, N. (Journal of Sports Sciences, 2016)
The objective of this 1-year, longitudinal study was to examine the development of perceived competence, tactical skills, motivation, technical skills, and speed and agility characteristics of young Finnish soccer players. We also examined associations between latent growth models of perceived competence and other recorded variables. Participants were 288 competitive male soccer players ranging from 12 to 14 years (12.7 ± 0.6) from 16 soccer clubs. Players completed the self-assessments of perceived competence, tactical skills, and motivation, and participated in technical, and speed and agility tests. Results of this study showed that players` levels of perceived competence, tactical skills, motivation, technical skills, and speed and agility characteristics remained relatively high and stable across the period of 1 year. Positive relationships were found between these levels and changes in perceived competence and motivation, and levels of perceived competence and speed and agility characteristics. Together these results illustrate the multi-dimensional nature of talent development processes in soccer. Moreover, it seems crucial in coaching to support the development of perceived competence and motivation in young soccer players and that it might be even more important in later maturing players.